Linking teacher self-efficacy and responsibility with teachers’ self-reported and student-reported motivating styles and student engagement - Lauermann, Fani; Berger, Jean-Louis (Learning and instruction, 2021)
Teachers' motivational beliefs—i.e., teachers' self-efficacy and felt responsibility for educational outcomes—can shape their professional decision-making and approaches to teaching. However, theorized associations with student outcomes remain elusive. In a multi-level analysis with 96 Swiss vocational teachers and their 1300 students, we examined the interrelations between teachers' self-efficacy, responsibility, teacher- and student-reported autonomy-supportive versus psychologically controlling teaching, and student motivation (emotional, behavioral, and cognitive engagement). Teachers' motivational beliefs predicted their endorsement of autonomy-supportive teaching, which in turn predicted student-reported autonomy support. Student-reported autonomy support was a powerful predictor of student engagement. Teachers’ motivational beliefs did not predict student-reported instructional practices and engagement directly, and indirect effects via teacher- and student-reported autonomy support were small. Teacher- and student-reported controlling practices were not significantly correlated. The degree of (mis)alignment of teacher- and student-reported instructional practices is a key ingredient in understanding the often missing link between teacher motivation and student outcomes. •Teacher efficacy and responsibility predicted teacher-reported autonomy support.•Large between-teacher differences in student-reported teaching practices emerged.•Teacher and student reports of autonomy support were positively correlated.•Student-reported autonomy support strongly positively predicted student engagement.•Teacher efficacy and responsibility did not predict student reports directly.